Phylogeny and origins of hantaviruses harbored by bats, insectivores, and rodents. - Wen-Ping Guo (Public Library of Science (PLoS), 2013)
Hantaviruses are among the most important zoonotic pathogens of humans and the subject of heightened global attention. Despite the importance of hantaviruses for public health, there is no consensus on their evolutionary history and especially the frequency of virus-host co-divergence versus cross-species virus transmission. Documenting the extent of hantavirus biodiversity, and particularly their range of mammalian hosts, is critical to resolving this issue. Here, we describe four novel hantaviruses (Huangpi virus, Lianghe virus, Longquan virus, and Yakeshi virus) sampled from bats and shrews in China, and which are distinct from other known hantaviruses. Huangpi virus was found in Pipistrellus abramus, Lianghe virus in Anourosorex squamipes, Longquan virus in Rhinolophus affinis, Rhinolophus sinicus, and Rhinolophus monoceros, and Yakeshi virus in Sorex isodon, respectively. A phylogenetic analysis of the available diversity of hantaviruses reveals the existence of four phylogroups that infect a range of mammalian hosts, as well as the occurrence of ancient reassortment events between the phylogroups. Notably, the phylogenetic histories of the viruses are not always congruent with those of their hosts, suggesting that cross-species transmission has played a major role during hantavirus evolution and at all taxonomic levels, although we also noted some evidence for virus-host co-divergence. Our phylogenetic analysis also suggests that hantaviruses might have first appeared in Chiroptera (bats) or Soricomorpha (moles and shrews), before emerging in rodent species. Overall, these data indicate that bats are likely to be important natural reservoir hosts of hantaviruses.